Experimental-clinical substantiation of principles of treatment ulcergastroduodenal bleedings at elderly and senile age - O. Ye. Skochilova (Бюллетень сибирской медицины, 2008)
Язвенные гастродуоденальные кровотечения, пожилой и старческий возраст, эндотоксемия